An update on Vitiligo pathogenesis. (15th December 2020) - Seneschal, Julien; Boniface, Katia; D'Arino, Andrea; Picardo, Mauro
Abstract: Vitiligo, the most common depigmenting disorder of the skin, is undergoing a period of intense advances in both disease understanding and therapeutic possibilities leading the way to the beginning of a new era for the disorder. Its pathophysiology has gathered the attention of researchers for years, and many advances have been made in the clarification of the interaction between different factors that result in depigmented macule formation. The complex interplay between non‐immunological and immunological factors in vitiligo is key for the development of the disease, and the participation of cells other than melanocytes, such as keratinocytes, fibroblasts, natural killer cells, and innate lymphoid cells, has been shown. Recent advances have also brought to the understanding of the complex part played by a specific subtype of T cells: T‐resident memory cells. This review analyzes some of the most recent insights in vitiligo pathogenesis underlining the interactions between different cell types, which are the basis for the therapeutic approaches under development.